Songs of the unsung : the musical and social journey of Horace Tapscott - Tapscott, Horace (E-Duke books scholarly collection., 2001)
"Songs of the Unsung is the autobiography of Los Angeles jazz musician and activist Horace Tapscott (1934-1999). A pianist who ardently believed in the power of music to connect people, Tapscott was a beloved and influential character who touched many yet has remained unknown to the majority of Americans. In addition to being "his" story, Songs of the Unsung is the story of Los Angeles's cultural and political evolution over the last half of the twentieth century, of the origins of many of the most important avant-garde musicians still on the scene today, and of a rich and varied body of music